Acetone-butanol-ethanol solvents improved enzymatic hydrolysis of pretreated energy grass. (1st June 2019) - Nan, Yufei; Yang, Ming; Xin, Donglin; Li, Kaijia; Kuittinen, Suvi; Pappinen, Ari; Zhang, Junhua
Highlights: The ABE solvents improved the hydrolysis efficiency of pretreated energy grasses. The promotional effect of solvent mixtures was dominated by butanol. Butanol increased the activity of EG II remaining in hydrolysis solution to 142.8%. The promotion of ABE solvents was conductive to effective utilization of enzymes. Abstract: Simultaneous saccharification and fermentation (SSF) is a promising process for conversion of lignocellulosic materials to biofuels. However, the fermentation end products might inhibit the saccharification of lignocellulosics by cellulose-degrading enzymes. This study investigated the effects of acetone-butanol-ethanol (ABE) fermentation products on enzymatic hydrolysis of energy grasses. After addition of 5 g/L butanol during the hydrolysis, the glucose yields of pretreated Hybrid Pennisetum and Avicel apparently increased from 62.8% and 33.4% to 77.5% and 63.8%, respectively. The acetone and ethanol also showed the promotional effect at higher concentrations (>10 g/L), but the acetic acid and butyric acid exhibited slight inhibition on the hydrolysis. The accumulative effect of these solvents was observed by addition of solvent mixtures. The ABE solvents improved the activity of cellobiohydrolase (CBH) I and endoglucanase (EG) II remaining in hydrolysis solution, particularly butanol increased the activity of EG II to 142.8%, which probably contributed to the enhanced hydrolysis. Thus, the inhibition of ABE end products on hydrolysis of lignocellulosic materials during SSF was negligible, but instead, the promotion on enzymatic hydrolysis provided an opportunity for effective utilization of enzymes.